Fostering students’ academic performance in physics using cognitive conflict instructional strategy and conceptual change pedagogy - Emmanuel E. Achor; Yakubu Peter Abuh (Association for Scientific Computing Electrical and Engineering(ASCEE), 2020)
This study investigated how to foster students' academic performance using cognitive conflict instructional strategy and conceptual change pedagogy on Senior Secondary (SS2) two in thermal physics in Kogi East Education Zone of Kogi State. The study adopted a quasi-experimental design, specifically, pretest-posttest non-equivalent-control group type. The study population was all the 7380 senior school two physics students in 153 co-educational secondary schools during the 2018/2019 academic session. The sample consisted of 294 SS two physics students (187 males and 107 females) drawn from six secondary schools using a multi-stage sampling technique. Thermal Physics Performance Test (TPPT) with reliability coefficients of 0.79 was used for data collection. Data collected were analyzed using mean, standard deviation, and bar graphs to answer the eight research questions and Analysis of Covariance (ANCOVA) to test the null hypotheses at 0.05 level of confidence. The study's findings revealed that there was a significant difference in mean academic performance among students taught thermal physics using cognitive conflict instructional strategy, conceptual change pedagogy, and traditional instructional strategy. The result equally revealed that cognitive conflict instructional strategy enhances students' academic performance more than conceptual change pedagogy. In addition, male and female students taught using cognitive conflict instructional strategy differ significantly in academic performance scores F (1, 99) = 24.409; p = 0.000 0.05. Likewise the male and female students taught using conceptual change pedagogy differ significantly in academic performance scores at F(1,95) = 33.974, p = 0.000 0.05. Furthermore the finding revealed that there is significant interaction effect of strategy and gender on students’ mean academic performance scores F (2, 293) = 6.307; p = 0.002 0.05. It was also found that both cognitive conflict instructional strategy and conceptual change pedagogy foster students' academic performance in Physics more than traditional instructional strategy. Based on the findings, it was recommended that Physics teachers be encouraged to use both cognitive conflict instructional strategy and conceptual change pedagogy to teach Physics in secondary schools to enhance students' academic performance.